Evaluation of risk associated with treatment of fat, oil, and grease: Grease interceptor from food processing industry effluent using bowtie analysis - Nurul Atikah, Azmi; Hanida, Abdul Aziz; Syamsul Bahari, Abdullah; Norhuda, Abdul Manaf; Tan, Lian See (American Institute of Chemical Engineers, 2024)
Fat, oil, and grease (FOG), a deposit in wastewater, develops from any processes in food and processing industries. FOG deposits in wastewater management systems can cause blockages in sewer systems. Grease Interceptor (GI) is one of the control measures to treat and prevent the blockage of FOG deposits in the sewer system. Nevertheless, few studies evaluate the extended hazard of GI application in FOG treatment. This study aims to assess the risk of GI in FOG treatment by using a bowtie technique. The hazard identified is FOG itself, whereas the top event was GI failure. The high contributions of the threats were an unsuitable variation of GI's type and design, no GI cleaning process schedule, and a clogged outflow pipe from GI. GI design according to standard and cleaning FOG deposits in GI by a licensed grease hauler were two suitable preventive barriers. The desludging process is essential to guarantee that the GI operates smoothly and is identified as an excellent recovery barrier. Inter-rater reliability (IRR) analysis to measure the consistency of their ratings on the data provided. The experts had a 75% overall agreement value of IRR risk rating value on assets, while 50% agreement value on people.